The variation of cystoliths and its taxonomic significance in Acanthaceae of Peninsular Malaysia - Siti Maisarah Zakaria,; Che Nurul Aini Che Amri,; Noraini Talip,; Abdul Latiff,; Amirul Aiman Ahmad Juhari,; Rozilawati Shahari,; Nur Shuhada Tajudin,; Mohamad Ruzi Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The foliar anatomical studies of 41 species of Acanthaceae from Peninsular Malaysia had been carried out. This study aims to identify the morphology and distributions of cystoliths in leaf anatomy and their taxonomic values in species studied of Acanthaceae. The foliar anatomical study involved procedures such as cross-section by using sliding microtomes on the petiole, lamina, and midrib, epidermal peel, leaf clearing, and observation under a light microscope. The finding in this study showed four types of cystoliths present in all species studied except in Acanthus, Staurogyne, Thunbergia, and Avicennia. Generally, they are present in lamina, petiole, and midrib but differ in shapes and sizes. Four types of cystolith cells are either solitary with round cystoliths, solitary with elongated cystoliths with blunt extremities, solitary with elongated cystoliths with one end pointed, or solitary with a point at both ends. However, this type of cystoliths is varied even within the same species either in petiole, midrib, or lamina. In conclusion, results showed that the occurrence and variation of cystolith cells have a taxonomic significance which can be used in identification and classification either at genus or species level in Acanthaceae.